2007
DOI: 10.1021/ie070437g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO2 Separation Selectivity in Oligo(ethylene glycol) Functionalized Room-Temperature Ionic Liquids

Abstract: Novel imidazolium-based room-temperature ionic liquids (RTILs) with one, two, or three oligo(ethylene glycol) substituents were synthesized. Solubilities and ideal solubility selectivities of CO 2 , N 2 , and CH 4 at low pressure (1 atm) in these RTILs were determined using a pressure decay technique. Comparison to corresponding alkyl analogues of these RTILs reveals similar levels of CO 2 solubility but lower solubilities of N 2 and CH 4 . As a consequence, RTILs with oligo(ethylene glycol) substituents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
304
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(315 citation statements)
references
References 45 publications
8
304
3
Order By: Relevance
“…Many research groups have conducted outstanding research on the physical absorption of CO 2 in ILs using both experimental and theoretical methods. [26][27][28][29][30] Their results have shown that CO 2 is very soluble in ILs, especially at high pressures. However, the physical absorption of CO 2 in ILs has some way to go because of their low capacity under atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have conducted outstanding research on the physical absorption of CO 2 in ILs using both experimental and theoretical methods. [26][27][28][29][30] Their results have shown that CO 2 is very soluble in ILs, especially at high pressures. However, the physical absorption of CO 2 in ILs has some way to go because of their low capacity under atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, also focused on imidazolium ILs, explored different structural variations of the cation in order to enhance CO 2 solubility and selectivity. [35][36][37] On the other hand, the performance of imidazolium-based ILs containing several different anions has also been evaluated. …”
Section: Introductionmentioning
confidence: 99%
“…This compound was prepared according to literature procedures [53] . For example, into a round-bottom flask equipped with a magnetic stirring bar, NaH (60 mg, 2.5 mmol), and dry THF (10 mL) were charged.…”
Section: Synthesis Of Poly(ethylene Glycol) Monomethyl Ether Imidazolmentioning
confidence: 99%